A Study on Drivers of Water Consumption in China From a Complex Network Perspective - Du, Ruijin; Zheng, Xiaoxia; Tian, Lixin; Liu, Kaihui; Qian, Lijuan; Wu, Qi; Fang, Guochang (Frontiers in Physics, 2021)
Water consumption has been one of the most important topics in the field of environment and economy. Even though the driving factors of water consumption have been well studied, it is still a daunting task to reveal the influence of the status of provinces in the entire supply chain. By combining the multi-regional input-output (MRIO) model and complex network theory, an inter-provincial virtual water transfer (VWT) network is constructed to analyze the overall structural characteristics of the network model and identify the structural roles of each province. The constructed inter-provincial VWT network exhibits the characteristics of a small-world network, that is, virtual water can be easily transferred from one province to another. Moreover, network analysis reveals that provinces with different positions in the VWT network play discrepant structural roles. Panel regression analysis is further used to quantify the impact of provincial structural roles on their water consumption. The results show that water consumption in China largely depends on some structural role characteristics in the VWT network. Out-degree and out-strength characterizing the ability of direct exporting virtual water exert significant positive influences, while in-closeness featuring the indirect virtual water importing rate has a significant negative effect on water usage. This indicates that adjusting the uneven provincial consumption structure, the direct production demand of downstream provinces and the indirect production activities in the supply chain can help reduce water consumption. Therefore, to come true the goal of water conservation in China, it is necessary to improve the trade structure between direct and indirect exporters and importers in the entire supply chain.